Hubungan Konsumsi Ultra-processed food dengan Hipertensi di Benua Amerika: Prisma Systematic Literature Review - Deni Nelissa; Dini Afriani Khasanah (CV. ITTC INDONESIA, 2026)
Background: Hypertension is one of the diseases that contributes significantly to morbidity and mortality due to cardiovascular complications. In the Americas, the prevalence of hypertension has increased alongside modern dietary changes, including the rising consumption of ultra-processed foods (UPF) that are high in sodium, sugar, and saturated fats. Evidence on the relationship between UPF consumption and hypertension risk in the adult population of the Americas remains fragmented and varies according to study design, location, type of UPF, and follow-up duration. Objective: This study aims to analyze and synthesize scientific evidence regarding the relationship between UPF consumption and hypertension in the adult population of the Americas through cross-sectional and longitudinal cohort studies. Methods: A Systematic Literature Review was conducted in March 2026 following PRISMA guidelines. Literature searches were performed in ScienceDirect, PubMed, ProQuest, and ClinicalKey, yielding 2,552 initial articles. After deduplication, title and abstract screening, and full-text evaluation, five articles met the inclusion criteria: (1) explicitly addressing UPF consumption; (2) reporting hypertension outcomes; (3) using cross-sectional, prospective, or cohort study designs; (4) published in peer-reviewed journals; and (5) available in full-text English. Results: Thematic analysis identified five main findings: (1) high UPF consumption is associated with an increased risk of hypertension; (2) consumption of unprocessed or minimally processed foods (U/MPF) is associated with a decreased risk of hypertension; (3) sugar-sweetened beverages, processed meats, and margarine are major contributors to hypertension risk; (4) the relationship between UPF consumption and hypertension is consistent across North and South America; and (5) the effect of UPF consumption on hypertension is evident in medium- to long-term analyses. Hypertension risk increased by up to 60% in the highest UPF consumption group, whereas high U/MPF intake reduced risk by up to 28%. Conclusion: High UPF consumption is consistently associated with an increased risk of hypertension, while U/MPF consumption exerts a protective effect on blood pressure. Certain types of UPF, such as sugar-sweetened beverages, processed meats, and margarine, contribute more substantially to hypertension risk, and this relationship is consistent across populations in the Americas. Long-term dietary interventions should focus on reducing UPF intake and increasing U/MPF consumption, supported by public education and food policies that limit UPF availability to prevent hypertension among adults in the Americas.